2007
DOI: 10.1088/0953-8984/19/37/376209
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of superconducting NbB2+xobtained from first-principles calculations

Abstract: First-principles calculations have been performed on NbB2+x to obtain its elastic constants using the plane wave pseudopotential method based on density functional theory, within the generalized gradient approximation. We have derived the bulk moduli, shear moduli, Young’s moduli, Poisson’s ratios and elastic anisotropies for NbB2+x polycrystalline aggregates. The elastic properties obtained here show that the structure becomes less symmetrical as the boron content increases. The higher elastic anisotropies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…It is confirmed in nuclear magnetic resonance (NMR) 11 and tun-nelling experiments, 12,13 as well as by recent calculations of the elastic properties. 14 Moreover, muon-spin rotation (µSR) experiments suggest that the superconducting gap is isotropic. 15 As is shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed in nuclear magnetic resonance (NMR) 11 and tun-nelling experiments, 12,13 as well as by recent calculations of the elastic properties. 14 Moreover, muon-spin rotation (µSR) experiments suggest that the superconducting gap is isotropic. 15 As is shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…A rule of mixtures calculation for each of the single-component diborides was used to estimate the Young's modulus for the HEB to be 501 ± 74 GPa, which is within 4% of the measured modulus of the ceramic. [13][14][15][16][17][18] The modulus of the HEB is higher than the modulus for WB 2 at 360 GPa, and close to the modulus of HfB 2 at 498 GPa. 14,16 TaB 2 , NbB 2 , and MoB 2 all have higher reported moduli at 519, 551, 512, and 569 GPa, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 64%
“…14,16 TaB 2 , NbB 2 , and MoB 2 all have higher reported moduli at 519, 551, 512, and 569 GPa, respectively. [13][14][15]18 Modulus values for MoB 2 and WB 2 were obtained from calculated values, while the remaining diborides were experimentally determined. Feng et al reported Young's modulus for an (Nb,Hf,Ta,Ti,Zr)B 2 ceramic to be 544 GPa measured using the impulse excitation method.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Among the transition-metal borides, NbB 2 -based materials are much less investigated as compared to ZrB 2 or TiB 2 -based ceramics, used for the applications in extreme environments. [1][2][3][4][5][6][7][8][9] Also, NbB 2 is considered as a potential candidate for the high-temperature structural applications, owing to its exclusive combination of properties viz. high melting temperature (3060°C), hardness (~21 GPa), elastic modulus (~540 GPa), moderate fracture toughness (~4 MPa.m 1/2 ), flexural strength (~400 MPa), thermal conductivity (~23 W/m-K), high electrical conductivity (~1.5 × 10 6 S/m), good chemical stability, and oxidation resistance in an oxidizing environment.…”
Section: Introductionmentioning
confidence: 99%